2015
DOI: 10.1007/s10847-015-0549-0
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of thermodynamic and structural properties of drug delivery system based on carbon nanotubes as a carboplatin drug carrier by molecular dynamics simulations

Abstract: Drug delivery is an important application of nanotechnology, in particular the targeted delivery of anticancer drugs using carbon nanotubes. To investigate the anticancer carboplatin's drug delivery system based on single-walled carbon nanotubes (SWCNTs), molecular dynamic (MD) simulations were applied to carboplatin filling inside pristine SWCNT and wrapping outside the pristine and functionalized SWCNT, and the drug in the free state. No significant difference was observed in the drug conformation in the fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 61 publications
(69 reference statements)
2
6
0
Order By: Relevance
“… 14 , 28 Other parameters were taken from the DREIDING force field and used in MD simulations. The structure of carboplatin was obtained from our previous works, 22 , 29 and the parameters were identified from the literature and the GAFF; 30 , 31 additionally, the carboplatins’ partial charges using the RESP module of AMBER 12 were calculated. The desired structures were immersed in a periodic water box of octagonal shape with a minimal distance of 12 Å from the system surface.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“… 14 , 28 Other parameters were taken from the DREIDING force field and used in MD simulations. The structure of carboplatin was obtained from our previous works, 22 , 29 and the parameters were identified from the literature and the GAFF; 30 , 31 additionally, the carboplatins’ partial charges using the RESP module of AMBER 12 were calculated. The desired structures were immersed in a periodic water box of octagonal shape with a minimal distance of 12 Å from the system surface.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, binding free energies were evaluated using the MM/PBSA (molecular mechanics/Poisson-Boltzmann surface area) method by previous experiment. 29 , 37 The analysis of the interaction energies between the nanotubes and the drug was accomplished with AmberTools14 and implementation of MMPBSA.py script.…”
Section: Methodsmentioning
confidence: 99%
“…Since these metallodrugs also induce tumor cell resistance and a number of side effects, such as the myelosuppression by cpx and the neurotoxicity by oxa, their encapsulation in carbon nanomaterials may also represent a promising strategy to overcome adverse effects. In this sense, numerous experimental and theoretical studies have demonstrated the potential of CNT as DDS for cpx and oxa by providing drug protection and a slow and concentrated drug delivery to the tumor sites. Similarly, the incorporation of cpx into boron nitride nanotubes (BNNT) has also been investigated in light of molecular dynamics (MD) simulations and density functional theory (DFT) calculations. However, presumably, there are no previous theoretical studies in the literature on the encapsulation of either oxa or cpx into CNH.…”
Section: Introductionmentioning
confidence: 99%
“…20 Previous studies indicate that the AMBER 12 simulation package has been used successfully for the study of the carbon nanotube structures. 21 Twenty CT molecules were added randomly around the NT1 and NT2 and the nanostructures were fully solvated with a cubic box of water, methanol and chloroform solvents, where the solvent molecule has a 15Å distance with the solute molecules. Structural parameters of the cathinone molecule, NT nanostructures and also the atomic charges of these molecules were obtained from DFT calculations at the M05-2X/6-31G(d,p) level of theory.…”
Section: Simulation Detailsmentioning
confidence: 99%